Investigation of Redox Shuttle Generation in LFP/Graphite and NMC811/Graphite Cells. Issue 4 (1st April 2022) - Boulanger, Thomas; Eldesoky, Ahmed; Buechele, Sebastian; Taskovic, Tina; Azam, Saad; Aiken, Connor; Logan, Eric; Metzger, Michael
Abstract : Unwanted redox shuttles can lead to self-discharge and inefficiency in lithium-ion cells. This study investigates the generation of a redox shuttle in LFP/graphite and NMC811/graphite pouch cells with common alkyl carbonate electrolyte. Visual inspection of the electrolyte extracted after formation at temperatures between 25 and 70 °C reveals strong discoloration. Such extracted electrolytes with intense red and brown color show relatively large shuttling currents in Al/Li coin cells. Two weight percent of vinylene carbonate is effective at preventing the redox shuttle generation as indicated by the absence of electrolyte discoloration and shuttling current. Ultra-high precision coulometry demonstrates that the presence of the shuttle molecule during cycling of LFP/graphite and NMC811/graphite pouch cells leads to significant charge endpoint capacity slippage and coulombic inefficiency. A brief constant voltage hold at 4.2 V can eliminate the shuttle molecule.